GA and ABA in Cucumber During Seed Development and Maturation - Chuanpis Aroonrungsikul; Sutavee Sukprakarn; Shoji Shigenaga; Siriporn Chumsangchoteakul (Agriculture and Natural Resources, 1994)
The physiological changes of Jed Bai and Puang cucumber seed were studied in rainy season during May August, 1991. Sed of both varieties reached its physiological maturity at 40 days after anthesis. The highest germination percentages of Jed Bai and Puang were obtained at 30 days and 25 days after anthesis, respectively while maximum viability was about 35 days after anthesis. Endogenous GA found in both varieties were GA1, GA3, GA4, GA7, GA19, GA20, GA24, and GA25. The highest total GA and ABA were obtained at 20 days after anthesis in both varieties but Jed Bai was higher in GA while Puang was higher in ABA than Jed Bai. First highest amount of ABA level was at 20 days after anthesis, the gradually decreased and peaked up again at 35 days after anthesis.